Apocynin Suppresses Lipopolysaccharide‐Induced Inflammatory Responses Through the Inhibition of MAP Kinase Signaling Pathway in RAW264.7 Cells. Issue 6 (4th August 2016) - Hwang, Young‐Jae; Lee, Sung Joon; Park, Jin‐Young; Chun, Wanjoo; Nam, Seung‐Joo; Park, Jin Myung; Park, Sung Chul; Choi, Dae Hee; Kang, Chang Don
ABSTRACT: Apocynin, an inhibitor of NADPH oxidase, exhibits anti‐inflammatory properties in ulcerative colitis. However, the underlying mechanism by which apocynin exerts this effect has not been clearly demonstrated. The objective of this study was to elucidate the anti‐inflammatory mechanism of apocynin in lipopolysaccharide (LPS)‐challenged RAW264.7 macrophage cells. Apocynin inhibited LPS‐induced extracellular secretion of the pro‐inflammatory mediators, nitric oxide (NO) and PGE2 and the expression of inducible nitric oxide synthase and cyclooxygenase‐2. Apocynin also suppressed LPS‐induced secretion of the pro‐inflammatory cytokine, tumor necrosis factor‐α and LPS‐induced degradation of IκB, which retains NF‐κB in the cytoplasm, consequently inhibiting the transcription of pro‐inflammatory genes by NF‐κB in the nucleus. To elucidate the underlying anti‐inflammatory mechanism of apocynin, the involvement of the mitogen‐activated protein (MAP) kinases, c‐jun N‐terminal kinase, extracellular signal‐regulated kinases, and p38 was examined. Apocynin attenuated LPS‐induced activation of all three MAP kinases in a concentration‐dependent manner. The present study demonstrates apocynin exerts anti‐inflammatory activity via the suppression of MAP kinase signaling pathways in LPS‐challenged RAW264.7 macrophage cells. Drug Dev Res, 2016. © 2016 Wiley Periodicals, Inc.